Implementation IBS Core Banking System with UTAUT Model to Understand Behavioral Intention - Saryadi; Murni Hastuti; Sundari; Erma Nurhayati Firdaus (LPPM Universitas Duta Bangsa Surakarta, 2021)
The goal of this study to know the influence Performance Expectancy, Effort Expectancy, Social Influences and Facilitating Conditions on Behavioral Intention in utilization application IBS Core Banking System at PT. BPR BKK Wonogiri. Population and sample in these study sum 49 responders with a census from response to existing questionnaires. Analyzed data used the multiple linier regression with validity reliability test, t-test, F-test, and coefficient determination. The result this study shows that effort expectancy and facilitating conditions have a positive and significance on behavioral intention, but performance expectancy and social influences have no significance effect on behavioral intention.